Performance evaluation of multiple lift push-pull LUO converters for automotive applications - Srinivasan, S; T. S. Sivakumaran, Dr (International Journal of Engineering and Technology, 2018)
Solar energy power generation has several advantages such as low maintenance costs; environment friendly, no rotating parts in construc-tion gives no noise. In recent years, solar power is used to charge the batteries of electric vehicles and instead of internal combustion En-gines the Electric motors such as DC motors, Brushless DC (BLDC) motors are used for driving the vehicles. The Multiple Lift Push-Pull Luo (MLPPL) converter is a DC-DC converter, which combines both switched capacitor and voltage lift techniques. Further, the MLPPL converters can be used in high power density, high power efficiency and voltage transfer gain applications. In this work, a MLPPL convert-er integrated with voltage source inverter (VSI) loading BLDC motor drive for automotive applications have been proposed. Further, the simulation of the proposed design has been carried out using MATLAB/Simulink Software. The torque of the BLDC motor has been varied and the performance of the MLPPL converter has been analyzed. Results demonstrate that the proposed design is capable to operate over a wide range of torque, which fulfills the application of Electric Vehicle.